Analysis of Hospital Readmission Patterns in Medicare Fee-for-Service and Medicare Advantage Beneficiaries. Issue 1 (January 2017) - Oh, Joobong June Park
Abstract : Purpose of Study: The study was conducted to examine the hospital readmission patterns of two groups of Medicare beneficiaries—those covered by traditional Medicare (Medicare fee-for-service [FFS]) and those enrolled in a Medicare risk plan (Medicare Advantage [MA])—and to determine the characteristics that significantly increase the likelihood of multiple hospital readmissions. Primary Practice Setting: The study setting is the Hospital of the University of Pennsylvania (HUP) located in Philadelphia, PA. Methodology and Sample: A retrospective descriptive study design was used to analyze the electronic data from the HUP information technology system for Medicare beneficiaries, 65 years and older, who had an index hospital admission at the HUP during 2012 (January 1, 2012, through December 31, 2012), and were subsequently readmitted one or more times to the HUP during the observation period. Results: FFS and MA beneficiaries were hospitalized an average of 1.5 (±1.0) times; 69% were rehospitalized once and 30% were rehospitalized two or more times. Characteristics that increased the likelihood of multiple hospital readmissions included being discharged on a weekend, admitted through the emergency department with a diagnosis of injury and poisoning, being diagnosed with a new problem of the circulatory system, having an exacerbation of a circulatory system illness, and having an infection related to a previous admission. Characteristics that decreased the likelihood of multiple hospital readmissions included being discharged to a skilled nursing facility and being discharged home with home health services. Implications for Case Management Practice: Identification of the risk factors and characteristics that increase the likelihood of multiple hospital readmissions will permit early interventions in discharge planning, as evidenced by decreasing the rate of hospital readmissions and the length of hospital stays, increasing in time to hospital readmission, and preventing the first readmission and a subsequent return to the hospital.